Development of Non-Text Teaching Materials to Enhance Social Care Attitudes in Elementary Schools - Nana Sutarna; Aim Abdulkarim; Bunyamin Maftuh; Kokom Komalasari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The purpose of this study is to develop non-text teaching materials based on the social capital of local wisdom, used as an alternative learning resource in elementary schools to foster students’ social care attitudes. This research employed the research and development (R&D) method. The Borg & Gall model served as the foundation, but for practicality, it adopted Sukmadinata’s simplification into three major stages: preliminary study, teaching material development, and effectiveness testing. The development of non-text teaching materials rooted in Kuningan’s local wisdom was carried out through stages of needs analysis, design, validation, revision, and trials, resulting in a final product ready for dissemination. The content was packaged in the form of 3D illustrated stories that highlight Kuningan’s cultural values such as gotong royong (mutual cooperation), silih asih-silih asah-silih asuh (mutual love, care, and guidance), and local traditions, with the aim of cultivating students’ social care attitudes. Expert validation indicated a high level of feasibility with minor revisions, while feedback from FGDs emphasized the need for reflective activities and a glossary. Both limited and extensive trials demonstrated that the teaching materials were well received by students, as evidenced by increased comprehension, engagement, and relevance. The effectiveness of the materials was supported by statistical data, where the experimental group’s N-Gain reached 51.16% (moderate) compared to the control group’s 8.91% (low), with the Mann-Whitney U test showing a significant difference in post-test results (p = 0.000). These findings align with Lickona’s character education theory and recent research affirming the importance of reinforcing local cultural values, making these materials strategic for fostering elementary students’ social care attitudes. This study demonstrates that non-text teaching materials based on local wisdom are effective in developing elementary students’ social care attitudes. The practical implication is that teachers can utilize them as contextual alternative learning media, while policymakers may adopt them as references for curriculum development grounded in local cultural values.